2018
DOI: 10.1590/0034-7167-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Aging demographic profile in municipalities in the state of Pará, Brazil

Abstract: There is heterogeneity in the population aging among the municipalities of Pará, mainly regarding socioeconomic conditions and number of people living in the municipalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…In Japan, this situation was related to thousands of premature deaths [22]. In the state of Para ´, a study observed that the purchasing power of the elderly as well as access to work and income were associated with greater survival of senior citizens and should be observed and promoted by public health policies [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, this situation was related to thousands of premature deaths [22]. In the state of Para ´, a study observed that the purchasing power of the elderly as well as access to work and income were associated with greater survival of senior citizens and should be observed and promoted by public health policies [23].…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, em 2010 os idosos representavam 8,6% da população geral, podendo em 2020 atingir 20%. Prevê-se que em 2050 que a população jovem com idade entre 0 e 14 anos representem 13,1% da população total, enquanto o estrato idoso (≥ 60 anos) atingirá 22,7%, justificando a inversão da pirâmide populacional 3,4,5 .…”
Section: Análisis Comparativo De La Calidad De Vida De Los Adultos Maunclassified
“…With technological and scientific advances in the field of health, longevity and increased life expectancy have become a significant reality in society. Population aging is a phenomenon characterized by an increase in the proportion of elderly people in relation to other age groups, leading to social and health service changes 1,2 . Aging is a natural and progressive process that occurs throughout life, resulting in biopsychosocial changes.…”
Section: Updatementioning
confidence: 99%